Online-Based Learning Problematics Between Needs, Readiness And Implications On The Purity Of Learning Outcomes - Eddy Saputra (Ilomata International Journal of Social Science, 2020)
ABSTRACT Online-based learning has been long echoed, online-based learning methods also have been implemented in several developed countries. In Indonesia it's self this method was already known as PJJ (distance learning). Does online based learning a necessity for students and teachers, while students and parents do not fully understand technology. then how the readiness technological infrastructure which includes the internet network, smartphones and laptops to support this learning, from the school and students. With the great distance between students and teachers, could online-based learning methods produce purity of learning outcomes. This paper will use qualitative methods, where data will be generated through observation, interviews and information from print and electronic media. The purpose of this paper is to map the problem of online base learning. at least, where one side of this method must be applied because of the pandemic period, on the other hand this method will not run optimally when conditions are normal. Keywords: online based learning, needs, purity of learning outcomes